2014
DOI: 10.1002/alr.21434
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis osteoblasts differ in cellular properties from normal bone

Abstract: To date, this is the first known study that shows a direct comparison of osteoblast properties between patients with and without CRS. Our results indicate that there are fundamental phenotypic differences in adhesion and mineralization between osteoblasts in patients with CRS compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Serum eosinophilia has also been linked with P‐glycoprotein levels and radiographic osteitis scores 668 . Early studies investigating the role of osteoblasts in sinus neo‐osteogenesis demonstrated decreased osteoblast adhesion and proliferation, and increased bone mineralization in CRS osteoblasts compared to controls 669 . More recently, Khalmuratova et al 670 reported an association between RUNX2 expression, a key osteoblast differentiation transcription factor, and neo‐osteogenesis, that was further activated by the proinflammatory cytokines IL‐13 and IL‐17A.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…Serum eosinophilia has also been linked with P‐glycoprotein levels and radiographic osteitis scores 668 . Early studies investigating the role of osteoblasts in sinus neo‐osteogenesis demonstrated decreased osteoblast adhesion and proliferation, and increased bone mineralization in CRS osteoblasts compared to controls 669 . More recently, Khalmuratova et al 670 reported an association between RUNX2 expression, a key osteoblast differentiation transcription factor, and neo‐osteogenesis, that was further activated by the proinflammatory cytokines IL‐13 and IL‐17A.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…Nonetheless, the severity of neoosteogenesis is considered as one of the predictors of postoperative re-stenosis, requiring the Draf III or modified Lothrop procedures, which involve the most challenging frontal sinus surgeries [6]. Notably, there are phenotypic differences in adhesion and mineralisation between osteoblasts in CRS patients when compared with control subjects [7]. These differences suggest that identification of the immunological and molecular mechanisms of osteoblast activation can be used to help understand neoosteogenesis and treat recalcitrant CRS.…”
Section: Introductionmentioning
confidence: 99%
“…Primary bone cells of CRSwNP were isolated as previously described 29,30 . Briefly, nasal poly‐ and soft tissues of sinus bone tissues were stripped using forceps.…”
Section: Methodsmentioning
confidence: 99%